Prototipe Turbin Angin Savonius Variasi Extra Layers Dengan Pengujian Real Wind Condition - Yudi Kurniawan; Ida Bagus Dharmawan; Zulkifli Zulkifli (Jurnal POLIMESIN, 2021)
Wind energy is renewable energy that is clean, environmentally friendly and easy to obtain. Balikpapan City is very suitable for applying the Savonius wind turbine because it has a relatively low average wind speed. Savonius wind turbine is a turbine consisting of two concave and convex blades that work based on drag forces. Savonius wind turbine can utilize wind energy at low speed 2 m/s to be converted into electrical energy which can reduce the electrical load in urban areas. This research makes a prototype of the Savonius wind turbine with the addition of variations extra layer on the concave turbine blades. The test method uses a generator that is attached to the turbine shaft and the test is carried out in a multi-storey building area. The results obtained are the Savonius wind turbine prototype capable of producing actual power 0.76 Watt and power coefficient is 0.082. The addition of an extra layer at both tips of the turbine concave blades is proven to be able to improve the performance of the Savonius wind turbine.